Implementation of School-Based Management in Improving the Quality of Educators - Riadiono, Riadiono; Fitria, Happy; Eddy, Syaiful (Journal of Social Work and Science Education, 2024)
The goal of this study is to provide an overview of school-based management planning, organization, execution, and assessment in junior high schools in Namang District, Central Bangka Regency. The teachers, committee members, and principals of SMP in Namang District, Central Bangka Regency, served as the study’s subjects. This study employed a qualitative descriptive methodology. According to the findings of a school-based study conducted in junior high schools in Namang District, Central Bangka Regency, management at these institutions begins with the overall plan, the vision, the mission, and the educational objectives of the institution. and starting with the position of each school principal as a leader and manager who has the primary responsibility for leading and has the policy to decide how this assessment process is carried out as best as possible, school-based management evaluation is done to improve the quality of educators.